Impacto de Transmilenio en el crimen de la Avenida Caracas y sus vecindades (2005)
In this paper, the implementation of the mass transport system Transmilenio on the Avenida Caracas, an avenue with high indexes of criminal activity in Bogotá, is taken as a natural experiment to overcome the simultaneity of crime and crimefighting policies. The study gauges the impact of urban transformation on crime on the Avenida Caracas and its neighboring areas. Through the use of spatial econometrics models and differences in differences methodology, the study measures the changes in the crime-levels in 65 geographic zones of Bogotá on the fringes of the Avenida Caracas. Data series were gathered that contain information regarding the exact geographic locations of the occurrences of 9 crimes studied in this analysis. These 9 crimes occurred between 1999-2002 in the afore mentioned 65 zones. Among the findings, the study shows criminal activity decreased significantly along the Avenida Caracas after the implementation of Transmilenio, even though the results vary in the remaining zones according to the type of crime committed and its proximity to the avenue. For each crime one can see evidence of displacement and deterrence of the criminal activity formally existent on the Avenida Caracas. There is also an evident absence of intertemporal spatial effects on homicides.